Differences in Baseline Characteristics and Access to Treatment of Newly Diagnosed Patients With IPF in the EMPIRE Countries - Kolonics-Farkas, Abigél Margit; Šterclová, Martina; Mogulkoc, Nesrin; Lewandowska, Katarzyna; Müller, Veronika; Hájková, Marta; Kramer, Mordechai; Jovanovic, Dragana; Tekavec-Trkanjec, Jasna; Studnicka, Michael; Stoeva, Natalia; Littnerová, Simona; et al. (Frontiers in Medicine, 2021)
Idiopathic pulmonary fibrosis (IPF) is a rare lung disease with poor prognosis. The diagnosis and treatment possibilities are dependent on the health systems of countries. Hence, comparison among countries is difficult due to data heterogeneity. Our aim was to analyse patients with IPF in Central and Eastern Europe using the uniform data from the European Multipartner IPF registry (EMPIRE), which at the time of analysis involved 10 countries. Newly diagnosed IPF patients (N = 2,492, between March 6, 2012 and May 12, 2020) from Czech Republic (N = 971, 39.0%), Turkey (N = 505, 20.3%), Poland (N = 285, 11.4%), Hungary (N = 216, 8.7%), Slovakia (N = 149, 6.0%), Israel (N = 120, 4.8%), Serbia (N = 95, 3.8%), Croatia (N = 87, 3.5%), Austria (N = 55, 2.2%), and Bulgaria (N = 9, 0.4%) were included, and Macedonia, while a member of the registry, was excluded from this analysis due to low number of cases (N = 5) at this timepoint. Baseline characteristics, smoking habit, comorbidities, lung function values, CO diffusion capacity, high-resolution CT (HRCT) pattern, and treatment data were analysed. Patients were significantly older in Austria than in the Czech Republic, Turkey, Hungary, Slovakia, Israel, and Serbia. Ever smokers were most common in Croatia (84.1%) and least frequent in Serbia (39.2%) and Slovakia (42.6%). The baseline forced vital capacity (FVC) was >80% in 44.6% of the patients, between 50 and 80% in 49.3%, and <50% in 6.1%. Most IPF patients with FVC >80% were registered in Poland (63%), while the least in Israel (25%). A typical usual interstitial pneumonia (UIP) pattern was present in 67.6% of all patients, ranging from 43.5% (Austria) to 77.2% (Poland). The majority of patients received antifibrotic therapy (64.5%); 37.4% used pirfenidone (range 7.4–39.8% between countries); and 34.9% nintedanib (range 12.6–56.0% between countries) treatment. In 6.8% of the cases, a therapy switch was initiated between the 2 antifibrotic agents. Significant differences in IPF patient characteristics and access to antifibrotic therapies exist in EMPIRE countries, which needs further investigation and strategies to improve and harmonize patient care and therapy availability in this region.